Nutritional Behaviors Pattern of High School Girls in North of Tehran - Shahnam Arshi; Bita Ghanbari; Kambiz Nemati; Yalda Soleiman Ekhtiari; Sharif Torkaman-nejad; Ali-Asghar Kolahi (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Healthy eating in adolescent girls has a crucial role in normal growth and reducing the incidence of chronic disease related to nutrition in adulthood. The purpose of this study was to determine high school girl's eating behaviors in north of Tehran. Materials and Methods: In this cross-sectional study, 722 female students who were selected randomly from public high schools in four districts of Tehran participated. Demographic variables and nutritional status were evaluated using systematic interviews with them by health professionals. Anthropometric parameters were also assessed. Results: Most girls (42.4%) had a normal BMI. The mean (SD) of daily consumption of fruits, vegetables and dairy products were 2 (1.1), 1.8 (1), 1.9 (1.07) servings, respectively. The mean (SD) of weekly intake of red meat, poultry, fish, eggs and beans were 3.08 (2), 3.15 (2.9), 0.95 (0.9), 2.6 (2.9) and 2.2 (1.2) times, respectively. The mean (SD) frequency of eating breakfast was 4.9 (2.6) times per week. 16.9% of girls never consumed fast foods. Girls who do not consume salty snacks and fast foods per week, had significantly normal BMI (p<0.05). Low-fat milk consumption, daily consumption breakfast and non consumption of fruits were significantly associated with social status (p<0.05). Do not eating breakfast had significant association with BMI (p<0.05). Conclusion: The consumption of major food groups in this study was lower than the recommended amounts. Further research is needed to determine enabling and reinforcing factors to healthy eating behaviors. Also, improvement attitudes and empowerment of adolescent girls to adopt healthy eating behaviors can be effective